2014
DOI: 10.1089/end.2014.0167
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy, Safety, and Costs of Percutaneous Occlusive Balloon Catheter-Assisted Ureteroscopic Lithotripsy for Large Impacted Proximal Ureteral Calculi: A Prospective, Randomized Study

Abstract: For large impacted proximal ureteral calculi, POBC-URSL was associated with a higher stone clearance rate, fewer complications and costs. POBC-URSL combined the advantages of URSL and PNL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Fig 1 shows the procedure of literature search and study selection. The studies consisted of five RCTs [ 12 16 ], one prospective [ 19 ] and four retrospective cohort studies [ 17 , 18 , 20 , 21 ]. Basic characteristics, such as age, sex ratio, stone size and stone side, were described comparable between rigid URSL and PCNL group in each study and the data was presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig 1 shows the procedure of literature search and study selection. The studies consisted of five RCTs [ 12 16 ], one prospective [ 19 ] and four retrospective cohort studies [ 17 , 18 , 20 , 21 ]. Basic characteristics, such as age, sex ratio, stone size and stone side, were described comparable between rigid URSL and PCNL group in each study and the data was presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Fig 2A showed that all of the RCTs described suggested randomization. Three studies [ 12 , 13 , 16 ] failed to report details about allocation concealment. It was quite difficult to perform blinding of participants or personnel in surgical treatment, so a high risk of bias was judged in this part for each study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of migration for impacted stones was much higher with much lower SFRs compared to migrated non-impacted stones. It could be that patients with impacted stone were more likely to have hydronephrosis or a higher degree of hydronephrosis resulting in a higher intra-operative migration rate [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…I then examined the original results of the works I mentioned above. It was reported that 20 patients who underwent URS need flexible ureteroscopy in the postoperative period, and none of the patients with PCNL required an auxilliary procedure in the study of Qi et al [2]. The data in meta-analysis belong to patients who do not need auxilliary procedure.…”
mentioning
confidence: 99%